1976
DOI: 10.1159/000127896
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Persistence of Hydroxyethyl Starch in Man

Abstract: In two groups, each consisting of five healthy volunteers, 7 ml blood/kg body weight were exchanged with equal amounts of hydroxyethyl starch (HES) and dextran 60 solutions, respectively. Dextran 60 plasma levels, determined by the anthrone method, were undetectable after 4 weeks. The elimination of HES from the blood, determined by an immunological technique and by the anthrone method, had a very protracted course. Two weeks after infusion the HES plasma concentrations were 9% of the initial value and after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
1

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(31 citation statements)
references
References 8 publications
3
27
0
1
Order By: Relevance
“…Consequently, the long-term exposure of cell cultures to 5 mg/ml FITC-HES results in a several fold increased uptake when compared to short-term incubation with even highest concentrations of 20 mg/ml. Regarding equivalent plasma levels of HES during different applications in vivo [24][25][26][27][28], it seems that intracellular accumulation of starch molecules may not play a role during acute volume resuscitation but appears to increase dramatically whenever HES is administered for several days even in small daily quantities.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the long-term exposure of cell cultures to 5 mg/ml FITC-HES results in a several fold increased uptake when compared to short-term incubation with even highest concentrations of 20 mg/ml. Regarding equivalent plasma levels of HES during different applications in vivo [24][25][26][27][28], it seems that intracellular accumulation of starch molecules may not play a role during acute volume resuscitation but appears to increase dramatically whenever HES is administered for several days even in small daily quantities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial predictions that over 99% of HES given to donors intravenously would be eliminated from their blood within 16 days [14], later studies showed that some HES remained in serum 17 weeks after ad ministration [15]. Even after 1 year, small amounts of HES could still be detected in leukapheresis donors' serum [2,3], The present study shows that HES given during low-dose HES leukapheresis is elim inated at a faster rate than previously re ported [2,3] for the standard, higher-dose procedure, although the HES employed was identical to the product used in previous studies (Volex, McGaw Laboratories).…”
Section: Discussionmentioning
confidence: 97%
“…Clinical plasma concentrations of HES are described as 5-20 mg/ml [11][12][13][14][15] . We chose the low concentration of 6 mg/ml because HES is widely used in small amounts to avoid side effects like bleeding complications [15,16] , renal impairment [17][18][19] and itching [20] .…”
Section: Discussionmentioning
confidence: 99%